Characterization of spatial patterns of dental restorative nanocomposites. Issue 7 (1st April 2019) - Ţălu, Ştefan; Stach, Sebastian; Lainović, Tijana; Blažić, Larisa
Abstract: The aim of this study was to provide important insights into the effects of four different dental polishing protocols (one single‐step and one multi‐step either followed or not by diamond paste polishing) on the 3D surface morphology of two representative dental resin‐based nanocomposites (a nanofilled and a nanohybrid composite) by means of digital image analysis and processing techniques. The 3D surface morphology was investigated by atomic force microscopy. Segmentation, statistics of height distributions (described by statistical parameters, according to ISO 25178‐2: 2012) and Minkowski functionals were applied to the images to characterize the spatial patterns of analyzed samples at micrometer scale. The nanofilled composite had significantly lower values of height parameters in comparison with nanohybrid one. Multi‐step polishing protocol generated a statistically significant smoother finish for both tested materials, than one‐step polishing protocol, even when it was followed by diamond paste polishing. Diamond paste polishing generated a statistically significant smoother surface of tested samples. This suite of surface analysis tools is important in the research and manufacture of these dental resin‐based nanocomposites, where material surfaces have a key role in the functionality of objects. Abstract : Minkowski volume V ( z ) (red lines), boundary length L ( z ) (green lines), and connectivity E ( z ) (blue lines) of the surface of nanofilled composite FUB polished by the multi‐step system. We investigated the morphological complexity of the 3D surface of nanohybrid and nanofilled dental restorative composites polished by single‐step and multi‐step systems. The 3D surface of the samples was measured using atomic force microscopy in contact mode. We determined the peak count histogram of the surfaces. We determined the Minkowski functionals S ( z ), L ( z ), and E ( z ) of the surface images.